Sintesis dan karakterisai kitosan dari limbah cangkang udang sebagai stabilizer terhadap Ag nanopartikel - Astuti Amin; Nur Khairi; Eko Allo (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The research of manufacturing chitosan from shrimp shell waste , and their use as a stabilizer in the manufacture of silver nanoparticles has been done. The aim of the research was to synthesize silver nanoparticles using chitosan as a stabilizer by chemical reduction method and determine the effect of chitosan concentration on the stability of Ag nanoparticles. In this study, the raw material used is shrimp shell powder and then processed in several stages, eliminating proteins, demineralization, and deacetylation. Chitosan obtained is 16.4 % of shrimp shell powder, with a degree of deacetylation of 85 %. Chitosan is used to synthesize silver nanoparticles as a reducing agent of silver ions in silver nitrate solution and is expected to be stabilizer. Sample containing 45 mg of chitosan and 1000 ppm AgNO3 has 421,60 nm of maximum wavelength, and the average particle size is 154.07 nm.